(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article observes rehabilitation models of providing services for people with disabilities, addictive behavior and people suffering from mental disorders in Germany. The author analyzes the systems of providing rehabilitation services to certain client groups and information systems of rehabilitation in the country. The aim of the study was to define the specific mechanisms of social policy and particular features of social security of persons with disabilities in Germany. The review of the information systems of rehabilitation, aimed on professional and social integration of people with disabilities (Rehadat) was also provided. The author describes the activities of different types of the rehabilitation centers for persons with disabilities and the system of inpatient psychosomatic rehabilitation. Determined the basic methods and ways of receiving the rehabilitation services for persons with addictions. Analyzed one of the most actual way of receiving the rehabilitation services – online service, electronic Rehabilitation Guide – Executive Rehab Guide. Conducted the analysis of existing effective methods of rehabilitation in the country, including the following: in-patient rehabilitation in the center, AA and alternative support groups, outpatient treatment in the community, counseling. Investigated the alternative approaches to rehabilitation the persons with addictive behavior – SMART Recovery (Self Management and Recovery Training) and the activity of boarding houses – Halfway houses.